2016
DOI: 10.12968/jowc.2016.25.sup2.s16
|View full text |Cite
|
Sign up to set email alerts
|

The presence of biofilm structures in atherosclerotic plaques of arteries from legs amputated as a complication of diabetic foot ulcers

Abstract: RAW and RDW have equity interest in PathoGenius, a clinical laboratory using DNA to identify microbes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…However, it is not known whether the bacteria are involved in initiation of plaque formation or colonize the plaques after they are formed. Recently, bacterial biofilms in atherosclerotic arteries have been identified by fluorescence microscopy and fluorescence in situ hybridization (FISH) [54,55]. This may indicate biofilms to be involved in the pathogenesis of atherosclerosis, and it is hypothesized that the presence of biofilm may contribute to enhanced risk of plaque rupture [55].…”
Section: Atherosclerosismentioning
confidence: 99%
“…However, it is not known whether the bacteria are involved in initiation of plaque formation or colonize the plaques after they are formed. Recently, bacterial biofilms in atherosclerotic arteries have been identified by fluorescence microscopy and fluorescence in situ hybridization (FISH) [54,55]. This may indicate biofilms to be involved in the pathogenesis of atherosclerosis, and it is hypothesized that the presence of biofilm may contribute to enhanced risk of plaque rupture [55].…”
Section: Atherosclerosismentioning
confidence: 99%
“…Of note, other reports have demonstrated that periodontal pathogens are also able to invade arterial walls and colonize atherosclerotic plaques [115,116,117,118]. In particular, recent data demonstrated that Porphyromonas gingivalis, one of the major pathogens involved in periodontal disease, induced platelets aggregation and the expression of several cell adhesion molecules, such as the intercellular adhesion molecule 1 (ICAM-1), the vascular cell adhesion molecule 1 (VCAM-1) and p-selectin.…”
Section: Mechanistic Model For the Relationship Between Periodontamentioning
confidence: 99%
“…While there are several reports on isolation of bacterial DNA from atherosclerotic tissue only a few recent studies have detected bacterial biofilms within atherosclerotic lesions [6, 13, 15]. In biofilm infections, microcolonies of bacteria become encased in a protective extracellular matrix consisting mainly of polysaccharides, proteins and DNA [16, 17].…”
Section: Introductionmentioning
confidence: 99%